The Medial Epicondyle-Ulnar Nerve Relation With Various Elbow Positions in Healthy Children - (:unkn) unknown (LIPPINCOTT WILLIAMS & WILKINS, 2014)
Background: The position of the ulnar nerve relative to the medial epicondyle in healthy children was determined with a high-resolution ultrasonography with elbow flexion, forearm pronation, and supination maneuvers which are commonly employed during reduction of the supracondylar humerus fractures. Methods: Healthy children aged between 4 and 12 years were enrolled in this study. Both elbows of the children were evaluated with a high-resolution sonography device with gradual flexion of the elbow, whereas the forearm is alternately in pronation and supination. The medial epicondyle-ulnar nerve distance was measured with the various positions of the elbow and the forearm. One-way analysis of variance was used to analyze the differences of medial epicondyle-ulnar nerve distance at different elbow flexion angles and forearm supination-pronation positions. Paried t test was used to compare the differences between the age and sex of the children. Results: Twelve female and 26 male children (76 elbows) with a mean age of 8.36 years were included in the study. Ulnar nerve was translated anteriorly through the medial epicondyle with increasing elbow flexion. The mean medial epicondyle-ulnar nerve distance that was 3.7 mm in an extended elbow decreased to 1.1 mm with full elbow flexion. The difference was statistically significant (P < 0.0001). Presence of the forearm in either supination or pronation did not produce a statistically significant difference. The age and sex of the children did not produce a statistically significance difference in medial epicondyle-ulnar nerve distance. Conclusions: Flexion of the elbow brings the ulnar nerve to a close proximity to the medial epicondyle independent of forearm pronation and supination in healthy children. The decrement of the medial epicondyle-ulnar nerve distance up to 1.1 mm a fully flexed elbow might be a factor that endangers the nerve during medial pinning in supracondylar humerus fractures.
Keywords: supracondylar fracture; ulnar nerve; medial epicondyle; SUPRACONDYLAR HUMERUS FRACTURES; K-WIRE FIXATION; INJURY; COMPLICATIONS